Business Strategy and Dynamics of Market Value in Financial Signaling and Information Asymmetries in Debt vs. Equity - Rana Shahid Imdad Akash; Aqsa Akbar; Muhammad Mudasar Ghafoor; Majid Imdad Khan (Journal of Management Practices, Humanities and Social Sciences, 2023)
The diversification strategies have important role in financial choices to decrease in cost and risk. In the previous empirical findings, the financial choices have little bit attention with reference to diversification strategies and market value behavior. The impact of corporate diversification is being explored in this study to find how they affect capital structure and firm value. This study used panel data analysis during period of 2012 -2022. It is suggested that corporate diversification strategy has significant impact on corporate financial structure and market value behavior. The increase in use of debt may be valid due to diversification strategies to eliminating the cost and risk. The product diversified firms, higher level of capital structure showed less risky as shown due to general asset specificity to more liquidity. The study aligned the cost with asymmetric risk and signaling trade off by concluding that the product and asset specificity diversification strongly related with capital structure. The funds managers, policy makers, regulators and other stakeholders may feel a safer flight in the implementation of diversification strategies and financial risk management while considering these capital structure choices.